Litostratigraphy, biostratigraphy and correlations of the sedimentary successions of the Neoproterozoic-Cambrian of the Rio de la Plata Craton (Uruguay and Argentina) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
We compare the litho-, bio- and chemostratigraphy of Neoproterozoic sedimentary successions of the Río de la Plata Craton, namely the Arroyo del Soldado Group (ASG) of Uruguay and the Sierras Bayas Group -Cerro Negro Formation (SBG-CNFm) of Tandilia (Argentina). Both successions are characterized by alternation of carbonates and siliciclastics (Poiré, 1987; Gaucher, 2000), as well as a geotectonic setting corresponding to a passive continental margin. The Yerbal, Polanco and Cerro Espuelitas Formations (ASG) are correlated lithostratigraphically to the Cerro Largo, Loma Negra and Cerro Negro Formations of Tandilia. Whereas the ASG is up to 5 km thick, the SBG-CNFm represents a strongly condensed section showing numerous erosive surfaces and only 350 m in thickness. This difference may be explained by the shallower, epicontinental sedimentary environment of the SBG-CNFm. The predominantly siliciclastic Yerbal and Cerro Largo Formations represent the transgression of the Vendian (Ediacaran) sea onto the Río de la Plata Craton. The overlying Polanco and Loma Negra Formations are characterized by thick and pure carbonate (especially limestone) deposits currently mined in both countries for use in the cement, lime and fertilizer industries. An expressive palaeokarst is developed on top of these carbonates, indicating sea-level drop and platform exposure (Barrio et al., 1991; Gaucher et al., 2004b). The lower Cerro Espuelitas Formation and the Cerro Negro Formation are made up of marls at the base, passing into shales and heterolithic facies up section.We report for the first time the occurrence of Cloudina cf. C. riemkeae Germs (1972) in micritic limestones of the Loma Negra Formation. This supports the correlation of this unit with the lower Polanco Formation, where these shelly fossils also occur (Gaucher y Sprechmann, 1999; Gaucher et al., 2003b). Moreover, Cloudina is currently regarded as an index fossil of the late Ediacaran (Grant, 1990; Amthor et al., 2003). Low diversity acritarch assemblages occur both in the ASG and SBG-CNFm. In the former, two assemblages were distinguished: a Bavlinella faveolata- Soldadophycus assemblage occurring mainly in the siliciclastic units, and a slightly more diverse Leiosphaeridia-Lophosphaeridium assemblage characteristic of the Polanco Formation (Gaucher, 2000). In the SBG-CNFm, the acritarch asemblage is sphaeromorph-dominated (mainly Leiosphaeridia), and similar to the Leiosphaeridia-Lophosphaeridium microflora of the ASG. For the first time we report acritarchs occurring in greenish pelites of the Villa Mónica Formation, assigned here to Leiosphaeridia minutissima, L. tenuissima and Synsphaeridium sp. These represent the oldest fossils so far reported from Argentina. Pothe de Baldis (1983) described Chuaria olavarriensis, Leiosphaeridia sp. and Paleorivularia ontarica from the upper Cerro Largo Formation. The former two taxa can be reassigned to Chuaria circularis and Leiosphaeridia minutissima, respectively. Palynological macerations of shales of the Cerro Largo Formation carried out in the present study yielded Leiosphaeridia tenuissima as dominant species, and a single vesicle assigned to Leiosphaeridia minutissima. A detailed micropalaeontological study is due to Cingolani et al. (1991), which describe the following acritarch species from the Cerro Negro Formation: Leiosphaeridia sp., Trachysphaeridium sp., Synsphaeridium sp. and granular sphaeromorphs grouped by the authors under «type A» acritarchs. The application of the currently accepted taxonomic criteria to these acritarchs allows assigning them to Leiosphaeridia jacutica, L. minutissima, L. tenuissima, Lophosphaeridium sp. and Synsphaeridium sp. In the present study, acritarchs assigned to Leiosphaeridia tenuissima were isolated from shales of the Cerro Negro Formation. Throughout the SBG-CNFm, a tendency towards smaller sphaeromorphs from base to top is observed: from 450 µm for Villa Mónica Formation to 380 µm for the Cerro Largo Formation and finally 200 µm for the Cerro Negro Formation. This trend has been reported for other shallow-water, marine Ediacaran successions elsewhere (Butterfield, 1997). On the basis of low diversity and dominance of sphaeromorphs, the acritarch assemblage of the SBG-CNFm can be assigned either to the Simple Leiosphere Palynoflora of Grey et al. (2003) or the younger Kotlin-Rovno assemblage of Vidal y Moczydlowska (1997). The palynoflora occurring in the lower and middle ASG has been correlated to the Kotlin-Rovno assemblage (Gaucher, 2000), supporting the lithostratigraphic correlation depicted above. Available chemostratigraphic data for the ASG and SBG-CNFm also suggest that the Loma Negra Formation correlates with the Polanco Formation. Whereas 87Sr/86Sr values for limestones of the Loma Negra Formation range between 0.7069 and 0.7087 (Kawashita et al., 1999b), limestones of the Polanco Formation yielded ratios between 0.7072 and 0.7085 (Kawashita et al., 1999a; Gaucher et al., 2004c). The Loma Negra Formation is further characterized by d13C values around +4 ‰ PDB (Gómez Peral et al., in press), which are similar to d13C relationships between +5.5 and 0 ‰ PDB reported for the lower Polanco Formation (Unit A of Gaucher et al., 2004b). Regarding the Villa Mónica Formation, available data are ambiguous regarding its age assignment and correlatios. On the one hand, stromatolite assemblages described from the unit (Poiré, 1987, 1993) suggest an upper Riphean age (Tonian or Cryogenian). On the other hand, the similarity of acritarch assemblages preserved throughout the SBGCNFm suggests that there is not a large time hyatus between the Villa Mónica and Cerro Largo Formations, raising the possibility of the Villa Mónica Formation being of Ediacaran age. The correlations here suggested imply that an extensive marine shelf developed on a large area of the Río de la Plata Craton in the late Ediacaran, possibly under tropical climate. According to Gaucher et al. (2003b), this shelf also included the Corumbá Group (Mato Grosso, Brazil), being thus at least 2500 km long.
Keywords: Neoproterozoic; Vendian; Ediacaran; Acritarchs; Argentina; Uruguay.